Pengaruh Fasilitas dan Kualitas Pelayanan Terhadap Loyalitas, Melalui Kepuasan Konsumen Sebagai Variabel Intervening pada Star Clean Car Wash Semarang - Indra Lutfi Sofyan; Ari Pradhanawati; Hari Susanta Nugraha (Universitas Diponegoro, 2013)
The background of the research is that the growing number of vehicles over the years, it is an opportunity for vehicles care services. The opportunities of the service industry it creating competition among service providers care vehicles. Therefore, the service provider have to increasing the dedication to create customer satisfaction. This research aimed to determine the effect of facilities and service quality towards loyalty through customer satisfaction as a variable intevening. The population is the consumers whom’d washed their vehicles at Star Clean Car Wash. The number of samples in this study was determined using Slovin formula that was selected to be a sample of 100 people. Sampling technique in this research is purposive sampling. Measurement scale using Likert scale. In the analysis of the data using simple linear regression and multiple regression test, with the application program SPSS 16.0. The results showed variable facilities effect on customer satisfaction by 42.9 percent. Variable service quality affects on customer satisfaction by 53.3 percent. Variables facilities and service quality affects on customer satisfaction by 56 percent. The variable service quality affect on loyalty by 43.8 percent. Variables facilities affect on loyalty by 43.4 percent. Variable service quality affects on loyalty by 37.1 percent. Variables facilities, service quality and customer satisfaction affect on loyalty by 51.5 percent. This study concluded that the variable facilities, service quality and satisfaction have positive and significant effect on loyalty. Star Clean Car Wash should be able to improve primary and complementary facilities, to always maintain the cleanliness and tidiness of the washing area, improve the appearance of the employees to be more interesting, and give more attention to consumers so that consumers feel appreciated.